Bagaimana Integrasi Green Business Mendorong Sustainability pada Agroindustri? Kajian Komprehensif Berbasis Analisis Bibliometrik - Septa Lukman Andes; Hendra Andiananta Pradana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
Growing consumer concern regarding sustainability issues has prompted companies to align their activities with environmentally oriented business practices, including in the agro-industrial sector. The concept of green business is considered relevant as a strategic framework for addressing these business challenges through the implementation of innovation, resource optimization, and a commitment to environmental responsibility. This study aims to observe the direction of scientific research development while mapping the main topic clusters of green business through a bibliometric approach. The method used is a systematic literature review of scientific articles in Scopus-indexed journals from 2016 to 2026, using the keywords green business, sustainability, and agroindustry. The bibliometric mapping process was conducted using the VOSviewer software. The results of the analysis indicate that there are three main, interrelated topic clusters: the impact of green business implementation, the integration of green business into business models, and the academic foundations of green business literature. The findings indicate that green business contributes to sustainability by aligning economic, environmental, and social dimensions. However, its effectiveness depends on organizational capabilities and institutional support. The findings are expected to contribute conceptually to the advancement of research on green business, while also serving as a foundation for designing adaptive, innovation-driven, and sustainability-oriented business strategies.